Study on the Risk Factors of Pulmonary Infection after Laparoscopic Surgery and Analysis of the Detection Results of Drug-Resistant Bacteria. (18th March 2022) - Zhai, Tingting; Zhang, Liwei; Sun, Jing; Li, Yuanchun; Hou, Jie; Du, Fengxia
Abstract : This study aimed to investigate and analyze the risk of pulmonary infection after laparoscopic surgery and the detection results of drug-resistant bacteria. With the laparoscopic technology developing rapidly in recent years and people's minimally invasive concept improving continuously, laparoscopic radical surgery has been widely used in the treatment of a variety of diseases. Laparoscopic surgery has the probability of causing complications. In order to avoid this, the risk factors after surgery were analyzed, and the drug-resistant bacteria were analyzed for accurate prevention and treatment. A total of 600 patients who underwent elective laparoscopic surgery in our hospital from January 2017 to September 2021 were included in the study. The risk factors and pathogen distribution of pulmonary infection were analyzed. The risk factors of pulmonary infection after laparoscopic surgery were hypoproteinemia, diabetes mellitus, pulmonary disease history, and perioperative blood transfusion. The main pathogens were Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Streptococcus pneumoniae . In clinical work, relevant nursing intervention measures can be developed for the above factors, so as to reduce the incidence of pulmonary infection. This study finds the risk factors for pulmonary infection after surgery, and the common drug-resistant bacteria has an indicative and guiding effect on the formulation of nursing management measures.